A light in the clouds - Esterhuizen, Margalith, 1927- 1927- (The Azrieli series of Holocaust survivor memoirs, 2022)
"Margalith Esterhuizen was born in Rădăuți, Romania, in 1927 and lived in both Cernăuți (now Chernivtsi) and Edineți during her childhood. She grew up in a contested area in Romania, the historical region of Bukovina, which was under Soviet control in summer 1940, and then reintegrated into Romania in summer 1941, when, as an ally of Nazi Germany, Romania retook the area. Margalith describes her life under the different regimes and how it felt as though her childhood ended that summer in 1941. Subject to increasing anti-Jewish laws and rampant antisemitism, and then forced from her home, when she and her family were evacuated and deported along with the Jewish community. They were marched to the area of Transnistria, an event that survivors and scholars have come to describe as a death march. Margalith ended up across in the village of Murafa, which became a ghetto for the Jewish deportees. In early 1944, Margalith was released--she writes about a negotiation between Zionist organizations and Romania to allow orphaned children to leave camps/ghettos in Transnistria. She was placed with foster families in Kishinev and Iasi for a short time and then she was put on a ship to Palestine in early May 1945, just before the official end of the war. The latter part of the memoir is about her postwar life in Israel and then in South Africa and Canada, featuring an emotional reunion in the early 1960s in Kiev (now Kyiv) with her father and stepmother. The Holocaust changed the course of Margalith's life and that of her family's--most of her relatives were killed, and she was indelibly marked by the separation from her father and stepmother."--